2002
DOI: 10.1159/000067903
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Classical Nuclear Transport Factors During Cellular Proliferation and Differentiation

Abstract: We recently cloned six human importin a proteins that transport specific substrates in complex with importin β into the nucleus. We now compared their absolute expression levels in different human cell lines. We examined their expression regulation during human cell proliferation and differentiation by means of specific antibodies. Proliferation inhibition by starvation of HeLa and HaCaT cells led to a marked decrease in the expression of various nuclear transport factors. In contrast, re-addition of serum inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 48 publications
4
48
1
1
Order By: Relevance
“…The findings were generally consistent with those reported by Koehler et al who demonstrated that importin proteins except for importin α5 were down-regulated in their expression in TPA-treated cells (11). A and B).…”
Section: Changes In Importin Expressionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings were generally consistent with those reported by Koehler et al who demonstrated that importin proteins except for importin α5 were down-regulated in their expression in TPA-treated cells (11). A and B).…”
Section: Changes In Importin Expressionsupporting
confidence: 92%
“…However, there has been no report describing the differentiation-associated changes in importin gene expression. The present study revealed the changes in gene expression compatible with the reported observations for protein expression (11). Thus, this is the first paper to describe the down-regulated gene expression of importins in association with differentiation toward the monocyte/macrophage lineage in HL-60 cells.…”
Section: Acknowledgementsupporting
confidence: 90%
See 2 more Smart Citations
“…It is widely accepted that Imp-␤ and some other Imp-␤ family carriers are abundant proteins in cells (44), but Imp-␤ is no more abundant than the other members of the family in our observation (data not shown). In addition, cellular contents of Imp-␣s are roughly comparable with that of Imp-␤, although expression levels of each of the family members vary in different cell types and tissues (7,(45)(46)(47). Therefore, it is not only the cellular concentration of carriers that determines import activity of each pathway.…”
Section: Discussionmentioning
confidence: 99%